Arctic Sea Ice Loss as a Potential Trigger for Central Pacific El Niño Events. Issue 7 (31st March 2020) - Kim, Hyerim; Yeh, Sang‐Wook; An, Soon‐Il; Park, Jae‐Heung; Kim, Baek‐Min; Baek, Eun‐Hyuk
Abstract: Little attention has been paid to the influence of Arctic sea ice loss on climate variability in the tropical Pacific. By analyzing observational data sets, we hypothesized that anomalous Arctic sea ice concentration variations have the potential to influence tropical Pacific sea surface temperature (SST) variability via atmosphere‐ocean coupled processes in the eastern subtropical North Pacific. To test this hypothesis, we conducted idealized model experiments with 15 ensembles in which historical SSTs for 1951–2016 were restored in the Arctic only with different initial conditions. We found that a positive phase of North Pacific Oscillation‐like atmospheric circulation, which is modulated by a sea ice reduction in the Pacific Arctic sector, triggers El Niño‐like warming in the central tropical Pacific. This implies that connections between the Arctic and the tropics should be considered for further understanding of changes in El Niño and other tropical Pacific climate variability in a changing climate. Key Points: Arctic sea ice concentration variations have the potential to influence tropical Pacific sea surface temperature A North Pacific Oscillation‐like atmospheric circulation triggers El Niño‐like warming in the central tropical Pacific through a SFM Connections between the Arctic and the tropics should be considered for further understanding of changes in ENSO in a warmer world